The Role of Teacher Training and Policy in Advancing Inclusive Education - SH, Ummi Aminah; Supriyono, Nanda Meg Ryan Puspitasari (Sinergi International Journal of Education, 2024)
This study examines the impact of teacher training and policy frameworks on the effectiveness of inclusive education through a systematic review of peer-reviewed literature. This study systematically reviews existing literature on inclusive education, examining key challenges, effective strategies, and policy implications. The review analyzed 68 peer-reviewed studies published between 2014 and 2024, selected from Scopus, Google Scholar, and PubMed. Inclusion criteria focused on studies addressing teacher preparedness, curriculum adaptation, or policy impacts on inclusive education. Studies without empirical data or relevance to students with special needs were excluded. Findings indicate that well-trained educators, robust policy frameworks, and adequate funding significantly enhance the effectiveness of inclusive education. Additionally, international comparisons reveal that countries with structured inclusive education policies achieve higher success rates in implementation. However, challenges persist, including inconsistencies in policy execution, limited resources, and gaps in teacher preparedness. Addressing these issues requires targeted interventions such as enhanced teacher training programs, increased funding, and greater collaboration among stakeholders. This study emphasizes the need for continued research on the long-term impacts of inclusive education and cross-cultural analyses to refine best practices. By addressing these challenges through evidence-based strategies, inclusive education can play a crucial role in promoting equity, diversity, and academic success for all learners.